Planificación turística para una gestión sostenible en destinos comunitarios de la provincia de Chimborazo. - Baños Mancero, Evelyn Madeline (2024)
Embargo de Publicación - Publicación de trabajo de titulación 05/12/2025 This is a study about the problem of tourism planning from a sustainable management approach of community destinations in Chimborazo province, Ecuador. The aim of the research is to design the tourism planning process based on the reality of these destinations. To achieve this, various methodologies were applied with a quantitative and descriptive approach, carrying out a study in the communities of Palacio Real and La Esperanza. These communities were a convenience sample due to their predisposition and commitment to collaborate in this study. The development of the research was based on a situational diagnosis in which natural and cultural factors, potentialities, problems and expectations that influence local tourism development were identified, as well as the impacts of tourism in these communities. Through the development of files, records and information gathering, it was observed that there are unique cultural and natural attractions, but due to the limitations in terms of management and planning criteria, these reveal the need to structure these processes, adjusted to the reality of community destinations with the objective of promoting their development.